(untitled) (Research, Society and Development, 2023)
This article addresses the treatment of depression, a globally prevalent psychiatric disorder, highlighting the emerging use of herbal medicines as an alternative to conventional antidepressants. The objective is to describe, through a literature review, the potential ways in which herbal medicines can be used for depression treatment, emphasizing the crucial role of the pharmacist in guiding the use of this class of medication. Based on a literature review, the study investigated medicinal plants such as saffron, ginseng, and Passiflora incarnata (passionflower), revealing promising results in terms of efficacy. However, controversy surrounding the use of these herbal medicines persists, attributed to a lack of familiarity among healthcare professionals and the need for standardization. The research underscores the importance of investing in regulation and continuing to explore the potential of these treatments.